Fundamental Bases of Success and Prestige of National Engineering Education - A. I. Rudskoy; S. V. Kabyshev; A. I. Borovkov; P. I. Romanov; N. S. Grishina (Высшее образование в России)
Currently, the educational community and the state are solving the task of creating a new nationally oriented system of engineering education. President of the Russian Federation Vladimir Putin noted: “We must rely on the fundamental bases of our education system, but look to the future, move forward, take the best that is in the world. And create your own.” In the article, the authors tried to answer the question: “What has underpinned the success and prestige and constitutes the fundamental bases of the national engineering education system?”. The main subject of analysis in the article is the normative legal acts of the Russian Empire and the USSR. The authors refer to the fundamental bases of engineering education only those components that have passed the test of time, post-revolutionary experiments during the change of historical epochs. Special attention is paid to the analysis of the negative experience of post-revolutionary experiments in the first third of the XX century. It is noted that the Soviet system, having gone through a series of post-revolutionary experiments of the 20s of the XX century, preserved and developed the original, unique features of the public education system of the Russian Empire. The authors presented these features, which form the basis for the success of the national education system, in the form of 9 theses. The abstracts were approved at a meeting of the Coordinating Council of the Ministry of Science and Education of the Russian Federation in the field of education “Engineering, Technology and Technical Sciences” within the framework of the round table of the Committee on Science and Higher Education of the State Duma of the Federal Assembly of the Russian Federation on “Improving the quality and increasing the prestige of engineering education in the Russian Federation” on June 17, 2024.